Non-passerine birds from Laguna Melincué Ramsar Site, Santa Fe province, Argentina - Romano, Marcelo (2015)
We present a waterbird inventory of the Laguna Melincué Ramsar Site in southern Santa Fe province, Argentina. We record 109 species from 28 families of non-passerine birds, including the 14 Nearctic species, four southern austral migrant species, three northern austral migrants, 17 partial migrants, and two altitudinal migrants. The eight most abundant species belong to different families and trophic groups. Thirty-six species were observed nesting or rearing chicks. This baseline knowledge of non-passerine birds will be useful to assist future conservation studies in this highly threatened area.